2010
DOI: 10.1007/s00277-010-1062-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the combination of bortezomib and dexamethasone in systemic AL amyloidosis

Abstract: Bortezomib -Dexamethasone (Btz/Dex) is an active regimen in patients with multiple myeloma and has been used in few patients with amyloidosis. Here we report a retrospective evaluation of the efficacy and toxicity of Btz/Dex in 26 patients with AL amyloidosis. 18 patients (69%) received Btz/Dex as first-line treatment. Organs most frequently involved were kidneys (100%) and heart (35%), 5 patients (19%) had > 2 organs involved. The overall response rate was 54% (14 of 26 patients), with 8 patients (31%) achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
17
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 19 publications
7
17
0
Order By: Relevance
“…20 A significantly higher CR rate was seen in patients treated upfront versus those at relapse (65.0% vs 21.7%; P ϭ .003). This appears superior to other studies in upfront-treated patients (for bortezomib and dexamethasone, RR ϭ 81% and CR ϭ 47%; for CTD, RR ϭ 70% and CR ϭ 27%) 11,21 or even autologous stem cell transplant, and is similar to previously documented experience with bortezomib-alkylator combinations (RR ϭ 90% and CR ϭ 62%). 3 In responding patients, the time to maximal response was 4.1 months (4.1 months upfront vs 4.2 months at relapse; P ϭ .95).…”
Section: Resultssupporting
confidence: 59%
See 3 more Smart Citations
“…20 A significantly higher CR rate was seen in patients treated upfront versus those at relapse (65.0% vs 21.7%; P ϭ .003). This appears superior to other studies in upfront-treated patients (for bortezomib and dexamethasone, RR ϭ 81% and CR ϭ 47%; for CTD, RR ϭ 70% and CR ϭ 27%) 11,21 or even autologous stem cell transplant, and is similar to previously documented experience with bortezomib-alkylator combinations (RR ϭ 90% and CR ϭ 62%). 3 In responding patients, the time to maximal response was 4.1 months (4.1 months upfront vs 4.2 months at relapse; P ϭ .95).…”
Section: Resultssupporting
confidence: 59%
“…This compares favorably with the 1-year PFS of 72.2%-74.6% seen in the recent phase prospective 1/2 trial of bortezomib. 4 Consistent with data published previously, 1,11,18,20,21,23 attaining a CR was correlated with a significant improvement in median PFS (not reached for patients in CR vs 17.5 months for those not in CR; 95% confidence interval, 8.5-26.5; P ϭ .002; Figure 1A) and for a VGPR-dFLC (not reached for VGPR-dFLC vs 9.1 months for non-VGPR patients; 95% CI, 6.0-12.2; P ϭ .026; Figure 1B). There was no significant difference in the median PFS between those attaining a CR and those with a VGPR-dFLC but not a CR (P ϭ .22), but small numbers and the retrospective nature of the study limit interpretation.…”
supporting
confidence: 81%
See 2 more Smart Citations
“…In this study, SAE were observed in 29% of cases, most common being fluid retention and hypotension, and TRM was 3% (Kastritis et al, 2010). A smaller series of patients (n = 26) was reported from a multicentre retrospective analysis outside the context of a clinical trial (Lamm et al, 2011) and showed similar results of 54% response and 31% CR with the use of BDex. In most clinical trials, patients with severe cardiac involvement are excluded.…”
Section: Bortezomibsupporting
confidence: 58%